The Impact of Transport Exclusion on the Socioeconomic Development of the Nowosądecki District - Szczecina, Katarzyna; Ziółko, Monika (Journal of Public Governance, 2023)
Objective: The aim of the article is to present the phenomenon of transport exclusion related to limited access to means of public transport and its impact on the socioeconomic development of the Nowosądecki district. The article also presents aspects related to social exclusion caused by limited access to work, education, health care, and recreation resulting from the lack of sufficient means of transport. Research Design & Methods: In order to achieve the assumed goal, the method of analysing the literature on the subject and empirical research in the quantitative approach (survey study) was used. Findings: The analysis of the research results showed that more than half of the respondents have problems with the use of public transport in the Nowosądecki district, which makes them feel excluded in terms of communication. Moreover, the conducted research proves that the main problem affecting the resignation from using public transport is the lack of direct connections between the place of residence and work, school, or recreation used by the respondents. The conducted research also showed a correlation between the respondents’ income and the frequency of using public transport; the higher the average monthly net income of the respondents, the less often they use public means of transport. Implications/Recommendations: The results of the survey showed that the inhabitants of the Nowosądecki district feel excluded in terms of communication. The existing transport system requires significant improvements in the functioning of public transport. Contribution/Value Added: The conducted research makes it possible to organise the knowledge on communication exclusion and its impact on the deepening of social exclusion. It also shows the motives of travellers when choosing a means of transport, thus indicating possible paths for further improvements in the transport system.